REAKSI PASAR MODAL INDONESIA TERHADAP PENGUMUMAN KEMENANGAN DONALD TRUMP DALAM PILPRES AMERIKA SERIKAT 2016 - Kusumayanti, Kadek Ria; Suarjaya, Anak Agung Gede (E-Jurnal Manajemen; Vol 7 No 4 (2018)DO - 10.24843/EJMUNUD.2018.v07.i04.p01, 2018)
The purpose of this research is to determine abnormal return which effected after announcement of Donald Trump winning on presidential election of United Stated 2016. This reseach use event study approaching, that used to test semi-strong market efficiency. Sample of this research are company that listed on LQ-45 index. Expected return in this study calculated using market-adjusted model. Based on t-test  found that there is market reaction in the announcement of Donald Trump winning on the presidential election of United Stated 2016. Market reaction can be know from significant abnormal return in H+1, H+3, H+4  and H+5. Significant abnormal return in H+3, H+4, and  H+5 imply market not efficient because there is long respons reaction.  Keywords : market reaction, semi-strong form market efficiency, political events .